Proyecto de inversión para la instalación de una planta procesadora de pulpa de maracuyá en el cantón Bolívar - Palacios Bravo, Yiria Vicenta (2013)
The purpose of this work was focused on developing a comprehensive analysis of the economic feasibility of installing a processing plant for passion fruit pulp in Bolívar Canton, using the crops of the area. This project comes with the idea of using passion fruit production, it can be used to benefit many Ecuadorian families and with possibility of extending to other places. The product development process, market research and financial economic study were realized to determine the feasibility of the plant using the software from CFN, REDATAM and SPSS. The results provided a positive NPV, meeting the expectations of the profitability for the business, with a 41% IRR which is higher than the discount rate; it has no negative operating cash flow in any period, no deficit in the final cash balance showing that operations will have no difficulties. The debt level limit is acceptable, the benefit-cost ratio is greater than one, the project has a positive net income, and capacity usage is consistent with the installed capacity.